Vinculación con la sociedad y universidad saludable - Hermida Bustos, César (2017)
This is a brief essay that tries to share the academic language with the population to inte-grate with the local actors, in a collective and participative way, the contributions of individ-ual research in concrete actions that benefit the social groups, as happened in the last cen-tury., When the solidarity revolution of women was born for their rights, the daily physical exercise for the care of the body and the defense of nature. The link with society is one of the three missionary components of the University, along with teaching and research. It gives the university the pertinence as a relation of the needs of the population with the pro-files of the careers. It is responsible for the link between academia and local human devel-opment, both urban and rural. This development is not exclusively economic, and it is in the hands of the local social organizations, the organized population, and depends on the role of the State.